Guidelines for Clostridium difficile infection in adults - Michał Kukla; Krystian Adrych; Agnieszka Dobrowolska; Tomasz Mach; Jarosław Reguła; Grażyna Rydzewska (Gastroenterology Review)
Clostridium difficile infection (CDI) has become a serious medical and epidemiological problem, especially in well developed countries. There has been evident increase in incidence and severity of CDI. Prevention, proper diagnosis and effective treatment are necessary to reduce the risk for the patients, deplete the spreading of infection and diminish the probability of recurrent infection. Antibiotics are the fundamental treatment of CDI. In patients who had recurrent CDI fecal microbiota transplantation seems to be promising and efficient strategy. These guidelines systematize existing data and include recent changes implemented in the management of CDI.